Introducing the crystalline phase of dicalcium phosphate monohydrate - Lu, B.Q.; Willhammar, T.; Sun, B.B.; Hedin, N.; Gale, Julian; Gebauer, Denis (NATURE PUBLISHING GROUP, 2020)
Calcium orthophosphates (CaPs) are important in geology, biomineralization, animal metabolism and biomedicine, and constitute a structurally and chemically diverse class of minerals. In the case of dicalcium phosphates, ever since brushite (CaHPO4·2H2O, dicalcium phosphate dihydrate, DCPD) and monetite (CaHPO4, dicalcium phosphate, DCP) were first described in 19th century, the form with intermediary chemical formula CaHPO4·H2O (dicalcium phosphate monohydrate, DCPM) has remained elusive. Here, we report the synthesis and crystal structure determination of DCPM. This form of CaP is found to crystallize from amorphous calcium hydrogen phosphate (ACHP) in water-poor environments. The crystal structure of DCPM is determined to show a layered structure with a monoclinic symmetry. DCPM is metastable in water, but can be stabilized by organics, and has a higher alkalinity than DCP and DCPD. This study serves as an inspiration for the future exploration of DCPM’s potential role in biomineralization, or biomedical applications.